ANALISIS PENDAPATAN USAHATANI KACANG TANAH DI DESA KANONANG SATU KECAMATAN KAWANGKOAN KABUPATEN MINAHASA (Income Analysis of Peanut Farming in Kanonang Satu Village Kawangkoan Sub District Minahasa Regency) - Ricky James Rawis; Theodora Katiandagho; Mex L. Sondakh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to analyze the magnitude of income level of a peanut farming in Kanonang Three Villages Kawangkoan Subdistrict. The research was carried out form October to November 2021. The data used in this study are primary and secondary data.The research result showed that occupational income is peanut in Kanonang Three Villages Kawangkoan Subdistrict so can he said it’s been to be profitable with more than Rp. 9.000.00 per hectare per annum season with the average monthly figure of more than Rp. 3.000.00 per hectare indicates that the average income per month would be sufficient compared with the regional minimum wage of Minahasa Regency, which is over Rp. 3.000.000.